Representasi Pesantren dalam Empat Film Religi Indonesia - Akhya Muhammad Khaidzir (Jurnal Komunikasi Islam, 2025)
This study explores the portrayal of Islamic boarding schools (pesantren), religious scholars (kiai), and Islamic students (santri) in Indonesian religious films, including 3 Doa 3 Cinta (2008), Perempuan Berkalung Sorban (2009), Negeri Lima Menara (2012), and Sang Kiai (2013). Through a qualitative-descriptive approach, the findings reveal that pesantren are often depicted as conservative educational institutions with challenging environments. However, the figure of the kiai is generally portrayed as a wise and open-minded leader who addresses socio-cultural issues and serves as a patriotic figure in Indonesia’s struggle for independence. The santri are commonly shown as resilient and united. Notably, Negeri Lima Menara presents a contrasting depiction by portraying Islamic boarding schools as modern educational institutions that play a significant role in shaping the nation’s future generation.